2017
DOI: 10.1080/14656566.2017.1350647
|View full text |Cite
|
Sign up to set email alerts
|

Considerations and treatment options for patients with comorbid atrial fibrillation and diabetes mellitus

Abstract: Atrial fibrillation (AF) and diabetes mellitus (DM) are common worldwide and their incidence is increasing, representing a significant public health and economic burden as well as an increase in individual increased morbidity and mortality risk profiles. Both conditions are closely related, as patients with DM are at increased risk of incident AF, and AF patients with DM are at higher risk of cardiovascular events compared to non-AF patients. Areas covered: This review article aims to provide an overview of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 122 publications
0
13
0
1
Order By: Relevance
“…We confirmed that HF events were significantly decreased in patients randomized to SGLT2 inhibitors. Reductions in both HF and AF/AFL and their concomitant interventions and downstream complications might subsequently reduce the risk of all-cause mortality in our present work [ 3 , 38 ]. In particular, we found that this effect could be enhanced with therapy of a longer duration.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that HF events were significantly decreased in patients randomized to SGLT2 inhibitors. Reductions in both HF and AF/AFL and their concomitant interventions and downstream complications might subsequently reduce the risk of all-cause mortality in our present work [ 3 , 38 ]. In particular, we found that this effect could be enhanced with therapy of a longer duration.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of its relationship with T2DM, AF should be appropriately managed. Therapeutic solutions include either rate control or rhythm control options and, in patients with CHA 2 DS 2 -VASc score of at least one point, anticoagulation agents should be prescribed to prevent thromboembolism and cardiovascular mortality (1,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is associated with higher risks of ischemic cardiovascular events, heart failure event irrespective to ischemic event, and mortality, and also a 40% higher risk of AF in the general population [ 4 7 ]. In patients with DM and established cardiovascular disease, those with AF at baseline had a higher risk of worse heart failure outcomes than those without AF [ 8 , 9 ]. Pathophysiological mechanisms including atrial electrical, structural, autonomic remodeling, oxidative stress, inflammation, and glycemic fluctuations have been suggested to explain the association between DM and occurrence of AF.…”
Section: Introductionmentioning
confidence: 99%